Kinetics of Adsorption in Mercury Removal Using Cassava (Manhiot esculenta) and Lemon (Citrus limonum) Wastes Modified with Citric Acid1 - Tejada, Candelaria (2015)
The high toxic concentrations of mercury in water bodies and its negative impact on the environment has resulted in the need for research on effective and low-cost methods for the treatment of industrial effluents, such as adsorption. This research compares the feasibility and viability of the adsorption abilities of cassava and lemon citric acid-modified peels. The results showed that the modified peel of cassava has a better adsorption ability compared to that of lemon. The kinetics models that best fit the experimental data were the Pseudo-second order model and the Elovich model for both modified biomasses. This means that the mechanism that controls the adsorption is a second order reaction, and also shows that the catalytic area of the adsorbent is heterogeneous; whereas the Freundlich isotherm describes better the adsorption process. In conclusion, the use of waste material is possible for Hg (II) removal. The study of chemical modifications is suggested to improve the adsorption percentages.